Respiratory–Swallow Coordination Training and Voluntary Cough Skill Training: A Single-Subject Treatment Study in a Person With Parkinson's Disease - Curtis, James A.; Dakin, Avery E.; Troche, Michelle S. (Journal of speech, language, and hearing research, 2020)
Purpose: Airway protective disorders are common in Parkinson's disease (PD), yet effective methods to rehabilitate these life-threatening impairments are limited. This study examined the effects of two skill-based treatments aimed at improving swallowing and cough in a severely dysphagic person with PD: respiratory-swallow coordination training (RSCT) and voluntary cough skill training (VCST). It was hypothesized that (a) RSCT would improve respiratory-swallow coordination and swallowing safety and efficiency and (b) VCST would improve reflex and voluntary cough effectiveness. Method: An 81-year-old man with midstage PD and severe dysphagia was recruited for study participation. The study utilized a multiple-baseline ABACA experimental design with a 2-month delayed retention assessment. Measures of respiratory--swallow coordination, swallowing safety and efficiency, and cough effectiveness were collected at each assessment using respiratory inductive plethysmography, flexible endoscopic evaluations of swallowing, and spirometry. Data were analyzed descriptively using baseline corrected tau and standard mean difference effect sizes (d). Results: Large effect sizes were observed immediately following RSCT for respiratory-swallow coordination (d = 9.17), penetration-aspiration (d = 12.88), vallecular residue (d = 1.75), piriform residue (d = 4.15), and overall dysphagia severity (d = 1.83). Large effect sizes were also observed immediately following VCST for single voluntary cough (d = 4.30), sequential voluntary cough (d = 3.28), and reflex cough (d = 5.58). Improvements were maintained 2 months later for all outcome measures except single voluntary cough. Discussion: This is the first study to examine the effects of RSCT and VCST in a person with PD. Robust improvements in respiratory-swallow coordination and swallowing safety and efficiency were achieved following four sessions of RSCT, and significant improvements in reflex and voluntary cough strength were seen following four sessions of VCST. Future work is needed to study these treatments in larger cohorts of people with PD.